Comparative Physiology of Energy Metabolism: Fishing for Endocrine Signals in the Early Vertebrate Pool - van de Pol, Iris; Flik, Gert; Gorissen, Marnix (Frontiers in Endocrinology, 2017)
Energy is the common currency of life. To guarantee a homeostatic supply of energy, multiple neuro-endocrine systems have evolved in vertebrates; systems that regulate food intake, metabolism, and distribution of energy. Even subtle (lasting) dysregulation of the delicate balance of energy intake and expenditure may result in severe pathologies. Feeding-related pathologies have fueled research on mammals, including of course the human species. The mechanisms regulating food intake and body mass are well-characterized in these vertebrates. The majority of animal life is ectothermic, only birds and mammals are endotherms. What can we learn from a (comparative) study on energy homeostasis in teleostean fishes, ectotherms, with a very different energy budget and expenditure? We present several adaptation strategies in fish. In recent years, the components that regulate food intake in fishes have been identified. Although there is homology of the major genetic machinery with mammals (i.e., there is a vertebrate blueprint), in many cases this does not imply analogy. Although both mammals and fish must gain their energy from food, the expenditure of the energy obtained is different. Mammals need to spend vast amounts of energy to maintain body temperature; fishes seem to utilize a broader metabolic range to their advantage. In this review, we briefly discuss ecto- and endothermy and their consequences for energy balance. Next, we argue that the evolution of endothermy and its (dis-)advantages may explain very different strategies in endocrine regulation of energy homeostasis among vertebrates. We follow a comparative and evolutionary line of thought: we discuss similarities and differences between fish and mammals. Moreover, given the extraordinary radiation of teleostean fishes (with an estimated number of 33,400 contemporary species, or over 50% of vertebrate life forms), we also compare strategies in energy homeostasis between teleostean species. We present recent developments in the field of (neuro)endocrine regulation of energy balance in teleosts, with a focus on leptin.